Degeneration of the olfactory guanylyl cyclase D gene during primate evolution. - Janet M Young; Hang Waters; Cora Dong; Hans-Jürgen Fülle; Emily R Liman (PLoS ONE)
Background The mammalian olfactory system consists of several subsystems that detect specific sets of chemical cues and underlie a variety of behavioral responses. Within the main olfactory epithelium at least three distinct types of chemosensory neurons can be defined by their expression of unique sets of signal transduction components. In rodents, one set of neurons expresses the olfactory-specific guanylyl cyclase (GC)-D gene (Gucy2d, guanylyl cyclase 2d) and other cell-type specific molecules. GC-D-positive neurons project their axons to a small group of atypical "necklace" glomeruli in the olfactory bulb, some of which are activated in response to suckling in neonatal rodents and to atmospheric CO2 in adult mice. Because GC-D is a pseudogene in humans, signaling through this system appears to have been lost at some point in primate evolution. Principal findings Here we used a combination of bioinformatic analysis of trace-archive and genome-assembly data and sequencing of PCR-amplified genomic DNA to determine when during primate evolution the functional gene was lost. Our analysis reveals that GC-D is a pseudogene in a large number of primate species, including apes, Old World and New World monkeys and tarsier. In contrast, the gene appears intact and has evolved under purifying selection in mouse, rat, dog, lemur and bushbaby. Conclusions These data suggest that signaling through GC-D-expressing cells was probably compromised more than 40 million years ago, prior to the divergence of New World monkeys from Old World monkeys and apes, and thus cannot be involved in chemosensation in most primates.